2018
DOI: 10.14245/ns.1836010.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recombinant Tyrosine Hydroxylase Expression on the Neurogenic Differentiation Potency of Mesenchymal Stem Cells

Abstract: ObjectiveTyrosine hydroxylase (TH) is a rate-limiting enzyme in dopamine synthesis, making the enhancement of its activity a target for ensuring sufficient dopamine levels. Rat bone marrow mesenchymal stem cells (rBM-MSCs) are known to synthesize TH after differentiating into neuronal cells through chemical induction, but the effect of its ectopic expression on these cells has not yet been determined. This study investigated the effects of ectopic recombinant TH expression on the stemness characteristics of rB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Immunofluorescence and quantitative RT-PCR analyses demonstrated an effective process of neuronal lineage induction of hASCs, especially after treatment with the Neu1 medium. In fact, the expression of TAU and TH, two mature neuronal markers, was increased in differentiated hASCs [ 49 ]. This last, TH, has been detected as an unequivocal sign of hASCs maturation towards dopaminergic cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence and quantitative RT-PCR analyses demonstrated an effective process of neuronal lineage induction of hASCs, especially after treatment with the Neu1 medium. In fact, the expression of TAU and TH, two mature neuronal markers, was increased in differentiated hASCs [ 49 ]. This last, TH, has been detected as an unequivocal sign of hASCs maturation towards dopaminergic cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…[KOU-HADYEK 6/5-2011]. rBM-MSCs used in this study was isolated and characterized in our previous study [14]. Briefly, MSCs were isolated from the bone marrow aspirates by gradient centrifugation (Ficollhistopaque gradient, 1.077 g/mL).…”
Section: Cell Culturementioning
confidence: 99%
“…Numerous studies have reported that exposure to these metals is toxic to the central nervous system and that disturbances in dopaminergic neurotransmission are important to the development of neurotoxicity [3][4][5][6]. Dopamine regulates various aspects of brain function and is synthesized by tyrosine hydroxylase (TH) [7,8]. During dopaminergic neurotransmission, extracellular dopamine secreted into the synaptic cleft is transported by the dopamine transporter (DAT).…”
Section: Introductionmentioning
confidence: 99%